2011
DOI: 10.1021/ct200320z
|View full text |Cite
|
Sign up to set email alerts
|

Solvation Structure and Dynamics of Ni2+(aq) from First Principles

Abstract: The aqueous solution of Ni(2+) was investigated using first principles molecular dynamics (FPMD) simulation based on periodic density-functional theory (DFT) calculations. The experimental structural parameters of the Ni(aq) complex are reproduced well by the simulation. An exchange event of the water molecule in the first solvation shell is observed, supporting the proposed dissociative mechanism of exchange. The calculated dynamic characteristics of the surrounding water molecules indicate too slow translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 78 publications
1
16
0
Order By: Relevance
“…All the BOMD trajectories are generated in the constant volume and constant temperature (NVT) ensemble, with the Nose–Hoover chain method for controlling the temperature of the system. The integration step is set as 1 fs, which has been proven to achieve sufficient energy conservation for the water systems . The total simulation times are 147 and 200 ps, respectively, assuring that the NH 2 can reach their equilibrium positions.…”
Section: Computation Methodsmentioning
confidence: 99%
“…All the BOMD trajectories are generated in the constant volume and constant temperature (NVT) ensemble, with the Nose–Hoover chain method for controlling the temperature of the system. The integration step is set as 1 fs, which has been proven to achieve sufficient energy conservation for the water systems . The total simulation times are 147 and 200 ps, respectively, assuring that the NH 2 can reach their equilibrium positions.…”
Section: Computation Methodsmentioning
confidence: 99%
“…The BLYP , exchange-correlation functional is used together with Grimme dispersion correction (D3) . We select the BLYP-D3 functional because it can properly describe systems with weak hydrogen-bonding interactions. A previous AIMD simulation study using BLYP-D3 also showed good agreement between the theoretical and experimental results of the electronic absorption spectrum of liquid water . In addition to the BLYP-D3 functional, the Perdew–Burke–Ernzerhof (PBE) exchange-correlation functional with Grimme dispersion correction (D3) is also considered for geometric optimization.…”
Section: Computational Methodsmentioning
confidence: 99%
“…44 Among the DFT work, we wish to mention in particular the paper by Mareš et al 45 who presented calculations of magnetic properties, including ZFS, for aqueous nickel(II) solutions. They combined the first-principles molecular dynamics for generating hydrated ion structures 46 with DFT calculations of the ZFS, in a similar way as in earlier work from our laboratory 15 but using the state-of-the-art methods of today.…”
Section: Introductionmentioning
confidence: 99%